MANAGEMENT OF SCOUT EXTRACURRICULAR ACTIVITIES IN IMPROVING STUDENT DISCIPLINE (CASE STUDY AT MADRASAH IBTIDAIYAH TWT BEDENGSATU) - Syarif Hidayat (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The school's way of facilitating student discipline is by holding Scout extracurricular activities. Management must be implemented in scout extracurriculars. The purpose of this research: (1) To analyze the planning of scout activities to improve discipline at Madrasah Ibtida'iyah TWT Bedengsatu for the 2022/2023 academic year. (2) To analyze the implementation of scout activities in improving the discipline of Madrasah Ibtida'iyah TWT Bedengsatu students for the 2022/2023 academic year (3) To evaluate scout activities in improving student discipline at Madrasah Ibtida'iyah TWT Bedengsatu for the 2022/2023 academic year This research uses a qualitative research approachcase study. The object of this research was carried out at MI TWT Bedengsatu. Data collection techniques use observation, interviews and documentation. The analysis techniques used in this research are data collection, data reduction, data presentation, drawing conclusions. The triangulation used to test the validity of the data is technique and source triangulation. The results of the research show that (1) Scout extracurricular management planning in increasing student discipline at Madrasah Ibtida'iyah TWT Bedengsatu is quite good because in the planning there are several areas of disciplinary activities, including holding Proker (work programs) for routine training every week, which followed by scout participants. (2) Implementation of scout extracurricular management in increasing student discipline at Madrasah Ibtida'iyah TWT Bedengsatu, namely that this implementation is a follow-up to the results of planning that has been implemented by Madrasah Ibtida'iyah TWT Bedengsatu. The standby members carry out the training that has been scheduled once a week properly and in an orderly manner, by carrying out the standby material taught by the scout leaders and trainers. (3) Evaluation of scout extracurricular management in increasing student discipline at Madrasah Ibtida'iyah TWT Bedengsatu. This evaluation activity is usually carried out in an activity usually called Fiska Mahmuka with an activity schedule once a year with the focus of the evaluation being the assessment of scout extracurricular activities in one year.